2016 IEEE 13th International Symposium on Biomedical Imaging (ISBI) 2016
DOI: 10.1109/isbi.2016.7493395
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of cortical sulci in 1,009 adults

Abstract: Specific genetic loci related to differences in brain anatomy have recently been discovered through efforts of the ENIGMA consortium and others. Yet different neuroanatomical traits may have different genetic determinants, and their discovery may offer a deeper understanding of genetic factors that shape the human brain. To investigate the degree of genetic contributions to variability in sulcal measures -the fissures within the brain's surface -1009 healthy young adult Australian twins and siblings were image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
2
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Here we show that most of the reliable sulcal shape descriptors are also under strong control. In four independent cohorts, we replicated prior findings 39,57,58 and analyzing more than a hundred sulci across the brain, we demonstrated the metrics of the central sulcus shape as the most highly heritable traits 39,57,58 . Heritability of sulcal width was also higher for the right hemisphere than the left hemisphere, consistent with the hypothesis that there is less genetic control over the left hemisphere 59 .…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Here we show that most of the reliable sulcal shape descriptors are also under strong control. In four independent cohorts, we replicated prior findings 39,57,58 and analyzing more than a hundred sulci across the brain, we demonstrated the metrics of the central sulcus shape as the most highly heritable traits 39,57,58 . Heritability of sulcal width was also higher for the right hemisphere than the left hemisphere, consistent with the hypothesis that there is less genetic control over the left hemisphere 59 .…”
Section: Discussionsupporting
confidence: 72%
“…The surface area is the total area of the sulcal surface. The enclosed CSF volume divided by the sulcal surface area gives the width, a gross approximation of the average width of the CSF in the fold 58 .…”
Section: Mri Image Processing and Sulcal Extractionmentioning
confidence: 99%
“…Many earlier works have focused exclusively on the central sulcus 37,40,61 . We have replicated findings of significant heritability in the central sulcus and further, showed that it is indeed the sulcus with the highest heritability estimate across the entire cortex.…”
Section: Discussionmentioning
confidence: 99%
“…The surface area is the total area of the sulcal surface. The enclosed cerebrospinal fluid (CSF) volume divided by the sulcal surface area gives the width, a gross approximation of the average width of the CSF in the fold 61 (see Supplementary Fig. 32 for a representation of sulcal shape descriptors).…”
Section: Methodsmentioning
confidence: 99%
“…"Sulcus-based morphometry" provides measures of the cortical fissures of the brain, which have been found to be associated with brain maturation (30), brain alteration with age or pathology (31,32) and correlated in a population of twins (33). We investigated sulci morphometry in controls and synesthetes based on shape descriptors (width, length, mean depth, and total surface area) analyzed for each sulcus.…”
Section: Sulci Extraction and Morphometrymentioning
confidence: 99%